1979
DOI: 10.1111/j.1365-246x.1979.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

The tidal field of a planet and the related intrinsic reference systems

Abstract: The tensor describing the tidal gravitational field of the Earth or of a planet is expressed in terms of the curvature parameters of the field.The tensor is then related to the orthonormal reference triads intrinsically defined within the gravity (or gravitational) field of the planet itself, i.e. the only triads recognizable locally with conceivable experiments: the canonical triad, for an observer connected with the Earth, and the tidal triad, for an observer in inertial navigation.Each system of orthonormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…where x1 = x, x2 = y and x3 = z, is the tidal potential used in geodetics (Marussi, 1979). In this case substitution yields…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…where x1 = x, x2 = y and x3 = z, is the tidal potential used in geodetics (Marussi, 1979). In this case substitution yields…”
Section: Theorymentioning
confidence: 99%
“…This allows the eigenvectors of Θ' to be identified as the tidal axes with directions given by (Marussi, 1979):…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In the same paper (Marussi 1979) it has also been shown that if a steady rotation is superposed to the residual field, the resulting potential W will be written as in which wl, w 2 , w 3 are the components of the rotation vector along the x-,yand z-axes respectively, w2 = w: + 0; + w:, and R the distance of a point P(x, y, z) from the rotation axis drawn through the centre of mass Po. The equipotential surfaces W again constitute a family of concentric homothetic quadrics, under circumstances hyperboloids or ellipsoids, which might degenerate into hyperbolic or elliptical cylinders, or even into a family of parallel planes.…”
mentioning
confidence: 89%
“…I have shown (Marussi 1979) that the microgravitational (or tidal) potential T of the residual field sensed by a satellite or in a spacecraft in inertial motion around a planet generating the gravitational potential V, is expressible in the neighbourhood of its centre of mass Po(O,O, 0) by g 2 T.= --(k1x2 t k2y2 -Hz2 t 2 f l~z + 2fZyz).…”
mentioning
confidence: 99%